Implementation of Guessing Game Instructional Approach to Teach English Vocabulary Mastery in Senior High School Students - Dwyka Lucky Pradana Putra; Riki Ruswandi; Hamdan Hidayat; Deri Supriatna (FKIP - Universitas Riau, 2026)
Vocabulary mastery is a fundamental aspect of English language learning, particularly in English as a Foreign Language (EFL) contexts. This study investigated the implementation of the Guessing Game Instructional Approach in teaching vocabulary mastery among senior high school students. A quasi-experimental design was employed involving 70 tenth-grade students at SMAN 1 Ciparay, consisting of an experimental group and a control group. Data were collected through pre-test and post-test vocabulary assessments and analyzed using descriptive and inferential statistics, including an independent samples t-test. The pre-test analysis revealed a significant baseline difference between groups, with the control group demonstrating higher initial vocabulary proficiency than the experimental group (p < .001). Post-test results also showed a significant difference (t = -5.74, p < .001), with the control group achieving a higher mean score (M = 89.11) than the experimental group (M = 60.09). Although students responded positively to the Guessing Game Instructional Approach, the findings suggest that it did not produce higher vocabulary achievement than conventional instruction. The study highlights the importance of considering initial group differences when evaluating instructional effectiveness.